Incorporation of cellulose fiber in glass ionomer cement. (28th January 2020) - Garoushi, Sufyan; He, Jingwei; Obradovic, Jasmina; Fardim, Pedro; Vallittu, Pekka K.; Lassila, Lippo
Abstract : This study investigated the effect of discontinuous cellulose microfibers with various loading fractions on selected physical properties of glass polyalkenoate (glass ionomer) cement (GIC). Fiber‐reinforced GIC (Exp‐GIC) was prepared by adding discontinuous cellulose microfiber (with an average length of 500 μ m) at various mass ratios (1, 2, 3, 4, and 5 mass%) to the powder of conventional GIC (GC Fuji IX) using a high‐speed mixing device. Fracture toughness, work of fracture, and compressive strength were determined for each experimental and control material. The specimens ( n = 6) were wet stored (37°C for 1 d) before testing. A scanning electron microscope equipped with an energy dispersive spectroscope was used to examine the surface of fibers after treatment with cement liquid. Data were analyzed using ANOVA . The Exp‐GIC (5 mass%) specimen had statistically significantly higher fracture toughness (0.9 MPa.m 1/2 ) than unreinforced material (0.4 MPa.m 1/2 ). On the other hand, Exp‐GIC with 1 mass% displayed the highest compressive strength (116 MPa) among all tested groups. The use of discontinuous cellulose microfibers with conventional GIC matrix considerably increased the toughening performance compared with the particulate GICs used.